2003
DOI: 10.1002/anie.200350903
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Isotope Effects on the Deslipping Reaction of Rotaxanes: High‐Precision Measurement of Steric Size

Abstract: Small structural changes can cause unexpectedly large effects on the deslipping reaction [1] of rotaxanes [2] (Scheme 1). A particularly striking example [3] is the replacement of the isophthalaldehyde unit in 6 a (Scheme 2) by a 2,6-pyridinedicarboxamide, that is, the simple exchange of a CH group by an isoelectronic N atom to yield 6 b. Without any other changes in the rotaxane structure, the barrier for the passage of the wheel over one of the stopper groups increases from approximately 80 to 135 kJ mol À… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
37
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(40 citation statements)
references
References 36 publications
3
37
0
Order By: Relevance
“…The rate-determining step of the deslipping reaction is the passage of the wheel over the stopper. The deslipping reaction has been used for determining steric size, and even the difference between CH 3 and CD 3 groups located at the stopper periphery affected the deslipping rate indicating the precision with which even small effects can be measured [9,10]. This result obtained through isotopic substitution, which affects the ratedetermining step of the deslipping reaction confirms the results presented here.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The rate-determining step of the deslipping reaction is the passage of the wheel over the stopper. The deslipping reaction has been used for determining steric size, and even the difference between CH 3 and CD 3 groups located at the stopper periphery affected the deslipping rate indicating the precision with which even small effects can be measured [9,10]. This result obtained through isotopic substitution, which affects the ratedetermining step of the deslipping reaction confirms the results presented here.…”
Section: Discussionsupporting
confidence: 87%
“…The aromatic rings in the wheel exert an anisotropy effect on the protons of the axle center pieces, and upfield shifts are usually observed that are also taken as evidence for rotaxane formation. They can be quite significant, and values of up to Dd ¼ 1:7 ppm have been observed [9,10]. Longer axles normally result in smaller values for SCHEME 1 Schematic illustration of the deslipping process.…”
Section: Resultsmentioning
confidence: 95%
“…Fujita et al [4] observed that the distortion of a cyclodextrin cavity could significantly restrict the guest rotation. Schalley et al [5] found that small structural changes such as the simple exchange of a CH group for an isoelectronic N atom could have unexpectedly large effects on the deslipping reactions of rotaxanes. We have previously reported a paraquat (N,NЈ-dimethyl-4,4Ј-bipyridium) substituent effect on complexation with a dibenzo-24-crown-8-based cryptand [6] and control of the complex-plexes" between BMP32C10 and paraquat derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…21,22 These results certainly stimulate the synthesis of optically active salen compounds with dendritic substituents at the EDA carbon positions and with various types of dendritic wedges, 23 starting from enantiopure D-and L-1,2-bis(2-hydroxyphenyl)ethylenediamine. 14b,c Scheme 1 Synthesis of N,N¢-disalicylidene-meso-1,2-bis(3,5-benzyloxydiphenyl)ethylenediamine (6) and N,N¢-disalicylidene-meso-1,2-bis(3,5-benzoyloxydiphenyl)ethylenediamine (7) …”
mentioning
confidence: 97%